2014
DOI: 10.1111/iwj.12308
|View full text |Cite
|
Sign up to set email alerts
|

A simple novel technique for enteroatmospheric fistulae: silicone fistula plug

Abstract: A simple novel technique for enteroatmospheric fistulae: silicone fistula plug. Int Wound J 2014; 11 (suppl. 1):22-24 AbstractEnteroatmospheric fistulae (EAFs), a rare condition that develops in patients treated with an open abdomen, present serious problems for the surgeon. There are no fixed algorithms for treatment of EAF, and treatment options are determined based on the experience of the surgeon and status of the patient. We developed a 'suspended silicone fistula plug' for treating a patient who develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Isolation of the gastrointestinal contents is one of the most important factors for preventing the spread of infections and for promoting wound healing. It has been demonstrated that NPWT under low intestinal pressure is effective for the management of fistulas [6, 7, 13]. In our patient, total parenteral nutrition was utilized to decrease the enteral pressure as well as the intestinal fluid secretion and to reduce the contamination of the wound and abdominal cavity with intestinal fluids.…”
Section: Discussionmentioning
confidence: 92%
“…Isolation of the gastrointestinal contents is one of the most important factors for preventing the spread of infections and for promoting wound healing. It has been demonstrated that NPWT under low intestinal pressure is effective for the management of fistulas [6, 7, 13]. In our patient, total parenteral nutrition was utilized to decrease the enteral pressure as well as the intestinal fluid secretion and to reduce the contamination of the wound and abdominal cavity with intestinal fluids.…”
Section: Discussionmentioning
confidence: 92%
“…Ramsay and Galo attempted to transform EAF into enterocutaneous fistula through a Foley catheter put into the fistula, which was taken out through a tunnel in the healthy tissues of the abdominal wall (33). Recently, Ozer et al, reported a successful closure in 1 patient by using of a novel "silicone fistula plug" technique (30). They used a circular silicone plug inserted in the fistula, which was suspended for an aluminium bridge over the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective, but not always possible, treatment of EAF is resection of the bowel segment harbouring the fistula opening . If this is impossible due to extensive peritoneal adhesions ( frozen abdomen) , bridging therapy is necessary until relaparotomy and elimination of the fistula can be achieved .…”
Section: Introductionmentioning
confidence: 99%